2009
DOI: 10.1007/s10530-009-9529-x
|View full text |Cite
|
Sign up to set email alerts
|

Prunus serotina unleashed: invader dominance after 70 years of forest development

Abstract: Propagule pressure and disturbance have both been found to facilitate invasion. Therefore, knowledge on the history of introduction and disturbance is vital for understanding an invasion process, and research should focus on areas in which the invasive species has not been deliberately introduced or managed to study unconfounded colonization patterns. Comparing the outcome of such spontaneous colonization processes for different ecosystems might provide a useful framework for setting management priorities for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Based on our work, current management techniques should focus on removal of edge populations, which serve as potential sources of spread into younger forests with more open canopies. High seed production at forest edges combined with the ability to form a seed bank may promote the spread of R. multiflora into forest interiors, as observed for other gap‐dependent invasive species (Vanhellemont et al, 2010). Once canopy gaps exist, areas should be monitored regularly to prevent new plants from becoming established and building reserves, since R. multiflora success in the understory is strongly linked to an open canopy (Matlack and Schaub, 2011) and declines with canopy growth (Banasiak and Meiners, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Based on our work, current management techniques should focus on removal of edge populations, which serve as potential sources of spread into younger forests with more open canopies. High seed production at forest edges combined with the ability to form a seed bank may promote the spread of R. multiflora into forest interiors, as observed for other gap‐dependent invasive species (Vanhellemont et al, 2010). Once canopy gaps exist, areas should be monitored regularly to prevent new plants from becoming established and building reserves, since R. multiflora success in the understory is strongly linked to an open canopy (Matlack and Schaub, 2011) and declines with canopy growth (Banasiak and Meiners, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Both species are among the 18 most invasive terrestrial plant species (DAISIE Project 2009). They are considered to be under the most aggressive exotic tree species in European forests and are regarded as strong competitors of native tree species (e.g., Kleinbauer et al 2010;Vanhellemont et al 2010). P. serotina was one of the first North American tree species that was introduced to Europe (Starfinger et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In its native range, P. mahaleb was shown to disperse seeds at considerable distances, reaching over 900 m, but local seed movements dominate, similarly to P. serotina (García et al 2007). The role of long distance dispersal is one of the focal points in studies on biological invasions, emphasizing the great invasive potential of frugivorous species (Von Der Lippe and Kowarik 2007; Vanhellemont et al 2010;Pergl et al 2011;Amodeo and Zalba 2013). Gosper et al (2005) showed that the structure of the landscape, i.e.…”
Section: Colonization In Agricultural Landscape Vs Forest Complexmentioning
confidence: 99%
“…7% of the stand. Studies on invasion patterns in P. serotina consistently report its high colonization effectiveness in Scots pine stands, or generally in coniferous stands and young forests, in contrast to lower effectiveness in fully developed forests and non-coniferous stands (Chabrerie et al 2007a(Chabrerie et al , 2007bVanhellemont et al 2009;Vanhellemont et al 2010;Jagodziński et al 2015). This trend reflects the divergent light conditions in these stands and light demands of black cherry, which attains highest growth, reproduction and probability of colonization in good light conditions (Closset-Kopp et al 2007;Knight et al 2008;Closset-Kopp et al 2011;Jagodziński et al 2015).…”
Section: Fsgs In Colonization and Established Populationmentioning
confidence: 99%
See 1 more Smart Citation